All creatures great & small. The complete series 6 collection [videorecording (DVD)] - Timothy, Christopher; Hardy, Robert, 1925-2017; Davison, Peter, 1951-; Drinkwater, Carol; Herriot, James (BBC Video ; Distributed by Warner Home Video, 2006)
"Series six continues the story of James Herriot (Christopher Timothy), his wife Helen (Lynda Bellingham) and his volatile but warm-hearted partner, Siegfried Farnon (Robert Hardy). The period is now the early fifties, and Siegfried pronounces great things for the forthcoming Elizabethan age."--Container.